PERSEPSI MAHASISWA PENDIDIKAN MATEMATIKA TERHADAP MANFAAT APLIKASI PHOTOMATH DALAM MENYELESAIKAN PERSOALAN MATEMATIKA - Wirda Jamiatul Sholeha; Granita (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This research explores how mathematics education students view the benefits of using the Photomath application in solving mathematics problems. The method applied is a qualitative research approach. Information was collected by distributing questionnaires to mathematics education students at the Sultan Syarif Kasim State Islamic University of Riau who had experience using Photomath to help them solve mathematical problems. A total of 30 subjek penetrants were the sample in this research. The collected data was analyzed based on perception themes related to the use of the Photomath application that had been determined by the researcher. The research results show that using the Photomath application is indeed suitable for making it easier for users to understand mathematical solving procedures both in terms of features and performance.